Pendampingan Program Inklusi Sosial pada Komunitas Perempuan Pembaca dalam Mewujudkan Kampung Tematik Hantaran Kota Surabaya - Syafi'i, Syafi'i; Novia Adibatus, Shofah (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Social welfare program can be achieved through the development of empowered and inclusive communities. However, women’s communities in Balongsari Subdistrict, Surabaya—particularly the Fatayat and Muslimat groups—face limitations in accessing literacy resources that support their social and economic empowerment. This study focuses on mentoring women reader communities through the Kampung Tematik Hantaran program as an effort to develop creative literacy and empower women. The program adopts the concept of a thematic village, focusing on hantaran (gift arrangements, commonly for weddings) as creative products with market potential. The approach used is Asset-Based Community Development (ABCD), which emphasizes the utilization of local assets as the foundation for community development. Community-based mentoring was conducted in RW 05 Balongsari, supported by the mobile literacy service LINKSMOKA. The results show increased skills in arranging hantaran, greater participation of women in local economic activities, and growing interest in reading as well as stronger social networks among community members. This mentoring initiative demonstrates that strengthening literacy and community-based creative economies can effectively promote sustainable social inclusion.